Al-Sulaymaniyah Tekkia as a station for Shami Pilgrimage during Ottoman Era (1516 AD-1918 AD) - Al-Rahhal, Amani Khalil (Journal of engineering sciences and information technology, 2024)
Damascus city developed clearly in the Ottoman period in the urban and architectural aspects, and the pilgrimage route had the largest role in the growth and expansion of the city towards the south. It’s one of the paths that reflects our historical heritage. Many Arab and Foreign researchers focused on the city expansion in the Ottoman period in that period. Other research focused on the Shami pilgrimage route. But in fact, this research aims to show the urban development of Damascus in the Ottoman period and the correlation between this development and the pilgrimage route. The research also aims to show the most important Islamic buildings in that period, which have been linked to preparing for the pilgrimage, such as Sulaymaniyah Tekkia which will be studied here, because it had a significant role in serving the pilgrims who stayed in Damascus during the preparation period of the pilgrimage, where the pilgrim used to spend several months before going to the Holy Land to perform the fifth pillar of Islam depending on various historical references , studies and analysis to take a complete subject includes the impact of hajj in the urban and architectural development in Damascus City and the appearance of the most important Islamic buildings which is designed to achieve the comfort of pilgrims, in addition to documented the pilgrimage route which the caravans of Hajj walked in Damascus to go to the land of Hejaz, with pictures and necessary maps. To reach finally to recommendations that aimed to reviving this route, registration it on the world heritage list, and the need to link the path of pilgrimage route with the Islamic buildings which were served the pilgrims who walked on it.
Keywords: Al-Sulaymaniyah Tekkia; Damascus; Hajj in the Ottoman period; Historical and Urban development; Islamic buildings in the Ottoman period; the Sham Pilgrimage route